Poverty as a Structural Barrier to Educational Equity in Indonesia - Alya, Rabiatul; Tiara, Veronika; Liska, Fransiska; Hafizi, M Zainul (Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
Poverty remains a fundamental structural barrier to achieving educational equity in Indonesia. This study aims to analyze how poverty affects access, participation, and the quality of education among low-income communities. Using a qualitative descriptive approach through literature review, the research identifies that economic hardship, inadequate infrastructure, limited digital access, and psychosocial stress significantly hinder educational opportunities for the poor. The findings reveal that poverty perpetuates intergenerational inequality by restricting learning opportunities and reducing human capital quality. The study concludes that inclusive educational reform, integrated with poverty alleviation policies and equitable resource distribution, is essential to breaking the cycle of deprivation and ensuring fair educational opportunities for all.